2019
DOI: 10.1097/xeb.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Conducting initial telephone consultations in primary care

Abstract: Background: Telephone consultations are increasingly used in primary care to deliver healthcare services to patients. However, there has been no review produced which identifies and maps the elements of the components, skills and training required for delivering telephone consultations in primary care. This review maps the evidence and can be used to inform clinical service and staff development.Method: A scoping review was conducted using Joanna Briggs Institute methodology. Inclusion criteria for this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, telephones have been used as a routine initial approach for accessing healthcare services for more than two decades. 1 Since the COVID-19 pandemic, the healthcare sector has seen increasing implementation of innovative technologies, particularly in telehealth—a umbrella term comprising telemedicine, electronic medical records, e-health, and other facets of health information technology. 2…”
Section: Introductionmentioning
confidence: 99%
“…However, telephones have been used as a routine initial approach for accessing healthcare services for more than two decades. 1 Since the COVID-19 pandemic, the healthcare sector has seen increasing implementation of innovative technologies, particularly in telehealth—a umbrella term comprising telemedicine, electronic medical records, e-health, and other facets of health information technology. 2…”
Section: Introductionmentioning
confidence: 99%
“…This wholesale introduction of online consultation whilst challenging, has demonstrated that effective care can be delivered remotely when supported by appropriate information and communication technology. Whilst some services had already integrated this mode of communication into existing pathways (Toon, 2002;Cooper and Alexander, 2019) and others were intending to adopt this approach in the longer term, the COVID-19 pandemic accelerated this transition with little time for preparation, training or opportunities to test the systems. It is therefore timely to appraise the benefits and shortcomings of using this type of technology to facilitate healthcare consultations.…”
Section: Introductionmentioning
confidence: 99%